Біопродуктивність та екосистемні функції м'яколистяних лісів Українського Полісся - Білоус, Андрій Михайлович (НУБіП України, 2016)
Дисертація на здобуття наукового ступеня доктора сільськогосподарських наук за спеціальностями 06.03.02 – лісовпорядкування та лісова таксація та 06.03.03 – лісознавство і лісівництво. – Національний університет біоресурсів і природокористування України, Київ, 2016. У дисертації представлено теоретико-методологічні та методичні засади дослідження біопродуктивності м’яколистяних лісів та автохтонних верб і систему нормативів для визначення екосистемних функцій лісів Betula pendula Roth, Alnus glutinosa (L.) Gaertn. та Populus tremula L. За результатами дослідження удосконалено теоретико-методологічні засади досліджень росту, розвитку і біопродуктивності лісів та створено методику дослідження надземної фітомаси кущів автохтонних верб. Розроблено методику дослідження надземної мортмаси лісу. Встановлено особливості росту і розвитку деревостанів, динаміки біопродуктивності березових, вільхових і осикових лісів. Визначено основні закономірності утворення мортмаси в м’яколистяних лісах, швидкість її деструкції та особливості формування мікобіоти. Розроблено нормативно-довідкову базу для визначення особливостей росту і розвитку деревостанів, динаміки фітомаси і мортмаси березових, вільхових і осикових лісів та оцінювання динаміки депонованого вуглецю, чистої первинної продукції, киснепродуктивності, енергоємності й енергопродуктивності та вмісту радіонуклідів 137Cs й 90Sr у компонентах фітомаси. Визначено загальний обсяг накопиченої органічної рослинної речовини, депонованого вуглецю, чистої первинної продукції, продукованого кисню та енергії в біомасі лісів Українського Полісся
Thesis for a degree of Doctor of Agricultural Sciences in specialty 06.03.02 – forest inventory and forest mensuration and 06.03.03 – forestry and silviculture.– National University of Life and Environmental Sciences of Ukraine, Kyiv, 2016. This thesis elaborates theoretical and methodological backgrounds, methodology approaches for the study of biological productivity of softwood deciduous forests and indigenous willows, and a system of reference tools and information to assess biophysical indicators of ecosystem functions of Betula pendula Roth, Alnus glutinosa (L.) Gaertn., and Populus tremula L. forests. Experimental background of the study includes: – 443 temporary sample plots allocated in softwood deciduous forests (incl. 152 sample plots in birch stands, 147 sample plots in alder stands, and 144 sample plots in aspen stands); 72 sample shrubs of indigenous willows (Salix cinerea L., Salix caprea L., Salix triandra L., Salix pentandra L.); – database "Forest Fund of Ukraine" by Production Association "Ukrderzhlisproekt", which contains characteristics of 937.8 thousand of primary inventory units of forest; – experimental site of 4.5 thousand ha for remote sensing studies of forest ecosystem. Subsequent to the study results, theoretical and methodological basis for investigation of forests growth and bioproductivity has been improved, and study procedure for aboveground bush live biomass of indigenous willows has been developed. The theoretical basis for classification of organic matter components of dead trees has been substantiated, and the study procedure for forest aboveground mortmass has been created. The analysis of forestry and measurement features of softwood deciduous forests of Ukrainian Polissya was performed. Growth and development peculiarities of mixed modal stands of birch, alder and aspen have been quantified. Models of the dynamics of forest stands were elaborated. Dynamics of bioproductivity of birch, alder and aspen forests by stand biomass components (stem, branches, foliage and roots), understorey and green forest floor was modeled. Analysis of the dynamics of softwood deciduous forests biomass structure was performed. Natural and basic wood and bark density of willows shoots and roots was quantified; besides, models of the total live biomass of shrubs in Ukrainian Polissya were developed based on the bush height and diameter. The main regularities of mortmass accumulation in softwood deciduous forests were defined. Mathematical models for evaluation of mortmass components (snags, logs, rough branch residues and fine litter) in oven-dry weight per 1 ha were elaborated. The models were elaborated using measurement indicators of birch, alder and aspen stands, including average height, average diameter and relative stocking of stands. In the conditions of Ukrainian Polissya (Chernihiv region), B. pendula logs wood decomposition rate is 0.128 yr-1, and total decomposition period of B. pendula coarse woody debris is 28–35 years. The logs of A. glutinosa decompose for 35–50 years at rate 0.070 yr-1. Logs of P. tremula decomposes for 24–30 years (0.134 yr-1). Stump mortmass decomposes considerably faster than other log components. Birch stumps decompose at rate 0.147 yr-1, alder stumps – 0.074 yr-1, and aspen stumps – 0.149 yr-1. Micobiota formation features based on mortmass of different degradation classes were described. Fungi belonging to Ascomycota and Basidiomycota divisions are most actively involved in B. pendula and P. tremula mortmass destruction. Only 2 % of the total mortmass of softwood deciduous forests is accounted during forest management inventory in Ukraine. Total pool of dead organic matter is estimated as 10.4 million tons of dry matter, including 46 % in birch stands, 50 % in alder stands and 4 % in aspen stands. The snags and logs comprise 22 % of the total mortmass, while mortmass of rough branch residues and fine litter comprises 9 % and 47 %, respectively. Studies of softwood deciduous forests bioproductivity were carried out employing system analysis approach and comprehensive observation using both in situ measurements and remote sensing. k-NN method applying Most Similar Neighbor classifier and data obtained from RapidEye (2011) and Ikonos (2012) satellite images were used for modeling of forest biomass spatial distribution at experimental site in Ukrainian Polyssia. The algorithms for determination of energy content in biomass were proposed. Energy output from wood and bark biomass components of B. pendula, A. glutinosa, P. tremula, S. cinerea, S. caprea and S. pentandra was investigated. The total energy of biomass of Ukrainian Polissya softwood deciduous forests is estimated as 1891 PJ. The peculiarities of 137Cs and 90Sr transfer from soil to biomass of wood and trunk bark, branches, foliage and roots of B. pendula, A. glutinosa, P. tremula; and dynamics of radionuclides in modal stands over age were investigated. 137Cs and 90Sr content in stem biomass of birch, alder and aspen at different soil contamination levels were measured. A set of regulatory-reference materials aimed to determine growth and development features of modal softwood deciduous forests, dynamics of live biomass and mortmass components of birch, alder and aspen stands, and to evaluate the dynamics of the carbon deposition, net primary production (NPP), oxygen and energy productivity, energy capacity and content of radionuclides 137Cs and 90Sr in forest biomass components has been elaborated for the purpose of applied system analysis of forest ecosystem functions and their practical use in forestry implementation. In total, softwood deciduous forests of Ukrainian Polissya produce about 4,0 Tg C·year-1 of NPP, which is about 27 % of the total NPP of all forests. NPP distribution by live biomass components of Ukrainian Polissya forests is typical for the temperate zone. Thus, 27 % of the total NPP is allocated in stems, 31 % – in roots, 16 % – in foliage, and 6 % – in branches. A considerable portion of NPP is contributed by understorey (5 %) and green forest floor (15 %). 226.4 Tg C is accumulated in the forest live biomass of Ukrainian Polissya, of which 68 % is allocated in stems, 8 % –in branches, 2 % –in foliage, 19 % – in roots, and 3 % – in the understorey and green forest floor. More than 20 % of total forest carbon pool is accumulated in biomass of softwood deciduous stands. Total oxygen production of Ukrainian Polissya forests is 43.07 million tons year-1, 15 % of which is produced by birch forests, 9 % – by alder forests, and 2 % – by aspen forests. The aspen forests are characterized by the greatest intensity of oxygen production (26.2 t·ha-1·yr-1)
Keywords: береза повисла; вільха клейка; осика; Українське Полісся; хід росту; біопродуктивність; фітомаса; мортмаса; мікобіота; екосистемні функції; депонований вуглець; киснепродуктивність; енергопродуктивність; 137Cs; 90Sr; модальні насадження; нормативно-довідкові матеріали; silver birch; black alder; aspen; Ukrainian Polissya; growth of forests; biological productivity